Inflated Grades, Enrollments & Budgets - J. E. Stone (Arizona State University, 1995)
Reports of the past 13 years that call attention to deficient academic standards in American higher education are enumerated. Particular attention is given the Wingspread Group's recent An American Imperative: Higher Expectations for Higher Education. Low academic standards, grade inflation, and budgetary incentives for increased enrollment are analyzed and a call is made for research at the state level. Reported trends in achievement and GPAs are extrapolated to Tennessee and combined with local data to support the inference that 15% of the state's present day college graduates would not have earned a diploma by mid 1960s standards. A conspicuous lack of interest by public oversight bodies is noted despite a growing public awareness of low academic expectations and lenient grading and an implicit budgetary impact of over $100 million. Various academic policies and the dynamics of bureaucratic control are discussed in relationship to the maintenance of academic standards. The disincentives for challenging course requirements and responsible grading are examined, and the growing movement to address academic quality issues through better training and supervision of faculty are critiqued. Recommendations that would encourage renewed academic integrity and make learning outcomes visible to students, parents, employers, and the taxpaying public are offered and briefly discussed.